PENGARUH IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE, INTELLECTUAL CAPITAL, DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Saputri, Elinda Dwi Agus; Fakhruddin, Iwan; Santoso, Suryo Budi; Dirgantari, Novi (ITB AAS Indonesia Surakarta, 2024)
The phenomenon in BUMN in 2023, namely PT Waskita Karya (Persero) Tbk. was dismissed by the IDX in stock trading because it was unable to pay its principal debt and overdue interest. The purpose of this study is to analyze the effect of good corporate governance, intellectual capital, and leverage on the financial performance of BUMN companies listed on the IDX in 2020-2022. This research uses quantitative methods processed using Eviews software. The results of this study are that the size of the board of commissioners has no effect on financial performance, the proportion of independent commissioners has a positive and significant effect on financial performance, the frequency of board meetings has a negative and significant effect on financial performance, intellectual capital has no significant effect on financial performance, and leverage has a positive and significant effect on financial performance. Keywords :Good corporate governance, intellectual capital, leverage, financial performance